Idiopathic Granulomatous Mastitis: A Case Report - Saad Younis; Emayof, Mardeya; Moner Hossen (AlQalam Journal of Medical and Applied Sciences, 2025)
Idiopathic granulomatous mastitis (IGM) is a rare, chronic, benign inflammatory disease of the breast. It is characterized by the development of a painful breast mass that gradually increases in size. Its etiology is unclear. It impacts women of reproductive age who have a history of pregnancy and lactation. Imaging findings were nonspecific; histopathologic examination is the best diagnosis. Its management combines surgery, antibiotics, corticosteroid therapy, and anti-inflammatories. We report a 38-year-old woman with a history of pregnancy and breastfeeding through the right side only presented with severe, increasing breast pain and noticed a small lump with tenderness and warmth; the physical examination revealed a mass with associated redness in the upper inner quadrant of her left breast. Ultrasonography revealed localized duct ectasia with mural thickening associated with an irregular hypoechoic mass, suggesting granulomatous mastitis. The true-cut biopsy confirmed the diagnosis. The abscess was evacuated through a minor incision performed under local anesthesia three times during 6 months, accompanied by antibiotic treatment. A treatment-free follow-up period resulted in significant improvement and complete resolution after 24 months. To validate the diagnosis of IGM, a thorough evaluation of possible etiologies is essential. Ultrasonography is the most common diagnostic modality. Histologically, it is characterized by neutrophils and the lack of caseous necrosis. Treatment is contentious, with surgical excision reserved for complex and refractory cases. Idiopathic granulomatous mastitis is a rare breast condition characterized by poorly understood causes and undefined treatment protocols. This condition warrants consideration in women of reproductive age. ‌التهاب الضرع الحبيبي مجهول السبب هو مرض التهابي حميد نادر ومزمن يصيب الثدي. يتميز بتطور كتلة مؤلمة في الثدي تزداد حجمها تدريجيًا. مسبباته غير واضحة. يصيب النساء في سن الإنجاب اللاتي لديهن تاريخ من الحمل والرضاعة. كانت نتائج التصوير غير محددة؛ الفحص النسيجي هو أفضل تشخيص. يجمع علاجه بين الجراحة والمضادات الحيوية وعلاج الكورتيكوستيرويد ومضادات الالتهاب. نعرض حالة امرأة تبلغ من العمر 38 عامًا ولديها تاريخ من الحمل والرضاعة التي كانت من خلال الجانب الأيمن فقط وجاءت مع ألم شديد ومتزايد في الثدي ولاحظت كتلة صغيرة مع رقة ودفء؛ كشف الفحص البدني عن كتلة مصحوبة باحمرار في الربع الداخلي العلوي من ثديها الأيسر. كشف التصوير بالموجات فوق الصوتية عن توسع موضعي في القناة مع سماكة جدارية مرتبطة بكتلة غير منتظمة ناقصة الصدى، مما يشير إلى التهاب الضرع الحبيبي. أكدت خزعة القطع الحقيقية التشخيص. تم إخلاء الخراج من خلال شق صغير تم إجراؤه تحت التخدير الموضعي ثلاث مرات خلال 6 أشهر، مصحوبًا بعلاج بالمضادات الحيوية. أدت فترة المتابعة الخالية من العلاج إلى تحسن كبير وحل كامل بعد 24 شهرًا. للتحقق من صحة تشخيص التهاب الضرع الحبيبي مجهول السبب، فإن التقييم الشامل للأسباب المحتملة أمر ضروري. الموجات فوق الصوتية هي الطريقة التشخيصية الأكثر شيوعًا من الناحية النسيجية؛ تتميز بالعدلات وغياب النخر الجبني. العلاج مثير للجدال، مع الاستئصال الجراحي المخصص للحالات المعقدة والمقاوم. التهاب الضرع الحبيبي مجهول السبب هو حالة نادرة في الثدي تتميز بأسباب غير مفهومة وبروتوكولات علاج غير محددة. تستحق هذه الحالة النظر فيها عند النساء في سن الإنجاب